Heterogeneous presentation of caspr2 antibody‐associated peripheral neuropathy – A case series. (30th April 2020) - Ellwardt, Erik; Geber, Christian; Lotz, Johannes; Birklein, Frank
Abstract: Contactin‐associated protein 2–like (caspr2) antibodies have been discovered recently. Since then a multitude of patients with caspr2 antibodies presenting with different neurological symptoms have been reported. Here, we describe three patients with caspr2 antibodies with different types of pain/no pain in combination with peripheral neuropathy. The first patient, a 33‐year‐old woman, presented with erythromelalgia‐like pain and autonomic symptoms; the second patient, a 58‐year‐old man, with paresthesia and pain while walking together with signs of peripheral motor neuron hyperexcitability in combination with optic neuritis, and the third patient, a 74‐year‐old man, without any pain but with polyneuropathy and encephalopathy. These cases illustrate the spectrum of symptoms in anti‐caspr2 diseases. The pain in such cases can be treated causally.